On Comparison Between Repetitive Controller and PI Controller Tracking Performance - Kurniawan, Edi (Pusat Penelitian Informatika - LIPI, 2014)
Tracking periodic signals are common task in many control problems. One of the examples is movement control of pick and place robot in industry. The requirement of high tracking accuracy becomes very important in many applications. Therefore, a sophisticated control algorithm that manages to achieve high accuracy tracking of periodic command is required. Repetitive Control (RC) based on internal model principle is one of control schemes that can be employed to achieve perfect tracking of periodic signal. On the other hand, Proportional Integral (PI) controller can also be used for tracking. This paper compares the tracking performance of PI controller, RC, and PI with RC, where PI with RC here is integration between PI controller and RC. Step by step design to obtain the parameters of PI, RC and PI with RC are given. A simulation on servo motor system is carried out to assess the performance of RC, PI, andPI with RC respectively. From the simulation results, the transient response and tracking accuracy are thoroughly discussed.